'My great hope in life is to have a house, a family and a daughter': relationships and sexuality in intellectually disabled people. (4th October 2014) - Rojas, Susana; Haya, Ignacio; Lázaro‐Visa, Susana
Abstract : Accessible summary: Relationships and sexuality are important for disabled people. Through the voices of 16 intellectually disabled adults, this paper shows what they consider to be important in areas such as education or personal relationships. Most of the people interviewed would like to have a partner and live together as a couple. Intellectually disabled people encounter many barriers to obtain certain basic rights. Summary: This study starts from the premise that we are sexual beings, and therefore, sexuality is part of our lives and defines us as human beings. This is also true with regard to intellectually disabled people. Within the framework of broader qualitative research carried out in Spain, some partial results of an ongoing study aimed at finding out what a group of adults see as important in different areas of their lives are presented here. Through the personal narratives of 16 intellectually disabled people, this paper explores some of their ideas and demands about sexuality and their sexual lives. Most of the people interviewed expressed their desire to have a partner and to live as a couple. There is no doubt that many intellectually disabled people have greater control over their lives and the decisions that affect them, but as they tell us, the presence of old ideas can hinder them from securing their fundamental rights.